2017
DOI: 10.1017/s0950268817002163
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination status and outcomes among influenza-associated hospitalizations in Columbus, Ohio (2012–2015)

Abstract: Prior studies suggest that the influenza vaccine is protective against some outcomes in hospitalized patients infected with influenza despite vaccination. We utilized surveillance data from Columbus, Ohio to investigate this association over multiple influenza seasons and age groups. Data on laboratory-confirmed influenza-associated hospitalizations were collected as a part of the Influenza Hospitalization Surveillance Project for the 2012-2013, 2013-2014, and 2014-2015 influenza seasons. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…This finding could be explained because vaccinated could attend to the hospital more frequently than do unvaccinated subjects as suggested by Casado et al 32 in a study carried out in older adults in 2013–2014 and 2014–2015 season. However, residual confounding by comorbid conditions could not be ruled out as suggested by other authors 33 because patients with comorbidities (79% in our study) are more likely to access healthcare resources and subsequently have more opportunities to receive the influenza vaccine. On the other hand, as suggested by Gutiérrez-González et al 17 because only hospitalized severe cases are included in the study, the protection for fatal episodes might be underestimated.…”
Section: Discussionmentioning
confidence: 93%
“…This finding could be explained because vaccinated could attend to the hospital more frequently than do unvaccinated subjects as suggested by Casado et al 32 in a study carried out in older adults in 2013–2014 and 2014–2015 season. However, residual confounding by comorbid conditions could not be ruled out as suggested by other authors 33 because patients with comorbidities (79% in our study) are more likely to access healthcare resources and subsequently have more opportunities to receive the influenza vaccine. On the other hand, as suggested by Gutiérrez-González et al 17 because only hospitalized severe cases are included in the study, the protection for fatal episodes might be underestimated.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it's unclear whether the potential benefits of NAIs seen in these studies would also apply to patients with non-pandemic strains of influenza or whether these benefits would be seen in vaccinated vs. unvaccinated patients. This is of importance as prior studies have demonstrated that influenza vaccination may protect against secondary pneumonia, but this may be dependent upon the circulating influenza strain [11]. Oseltamivir is generally well-tolerated; however, neuropsychiatric events such as delirium, hallucinations, and behavioral changes or rare dermatologic reactions (e.g.…”
Section: Oseltamivirmentioning
confidence: 99%
“…Limited data exist regarding absorption of oseltamivir and drug concentrations in critically ill patients with one pharmacokinetic study suggesting drug concentrations obtained in critically ill patients do not differ from ambulatory patients as described above [11]. Furthermore, there is no evidence to suggest differences in clinical outcomes based on oseltamivir dose.…”
Section: High-dose Oseltamivirmentioning
confidence: 99%